Trends of minimum temperatures in Maribor - Žiberna, Igor; Ivajnšič, Danijel (Journal for Geography, 2019)
The article analyses the minimum temperature trends at the Maribor-Tabor meteorological station in the period 1961-2019. The minimum temperatures rise at a higher rate than the maximum temperatures, which is a result of the interaction of global climate change and the intensification of the urban heat island phenomenon. Trends in the number of days with minimum temperatures below -10.0 °C, the number of days with minimum temperatures below 0.0 °C (cold days), the number of days with maximum temperatures below 0.0 °C (ice days) and the number of days with minimum temperatures above 20.0 °C (tropical nights) are also analysed. Data show a markedly lower number of days with a minimum temperature below -10.0 ° C and a higher number of tropical nights. The frequency of tropical nights is increasing at an exponential rate. These trends otherwise affect the shortening of the heating season and lower heating costs in winter, but in summer, due to increased stress, reduce the quality of the living environment. Thus, people with health issues, the elderly, children and pregnant women are additionally exposed to heat stress, which may even increase mortality.